The immune response in canine and human leishmaniasis and how this influences the diagnosis- a review and assessment of recent research - Ivănescu, Larisa; Andronic, Bianca Lavinia; Grigore-Hristodorescu, Smaranda; Martinescu, Gabriela Victoria; Mîndru, Raluca; Miron, Liviu (Frontiers in Cellular and Infection Microbiology, 2023)
Leishmaniasis is a widespread but still underdiagnosed parasitic disease that affects both humans and animals. There are at least 20 pathogenic species of Leishmania, most of them being zoonotic. The diagnosis of leishmaniasis remains a major challenge, with an important role being played by the species of parasites involved, the genetic background, the immunocompetence of the host. This paper brings to the fore the sensitivity of the balance in canine and human leishmaniasis and addresses the importance of the host’s immune response in establishing a correct diagnosis, especially in certain cases of asymptomatic leishmaniasis, or in the situation the host is immunosuppressed or acquired leishmaniasis through vertical transmission. The methods considered as a reference in the diagnosis of leishmaniasis no longer present certainty, the diagnosis being influenced mostly by the immune response of the host, which differs according to the presence of other associated diseases or even according to the breed in dogs. Consequently, the diagnosis and surveillance of leishmaniasis cases remains an open topic, requiring new diagnostic methods adapted to the immunological state of the host.